Impact of COVID-19 Pandemic on Elevated Anxiety Symptoms of Maintenance Hemodialysis Patients in China: A One-Year Follow-Up Study - Lv, Honghong; Meng, Junping; Chen, Yang; Yang, Feng; Wang, Wen; Wei, Guohua; Zhang, Jiaojiao; Wang, Huan; Wang, Mengqiu; Zhou, Lu; Liu, Hongbao (Frontiers in Psychiatry, 2022)
Recent studies have shown that coronavirus disease 2019 (COVID-19) aggravates anxiety in patients with maintenance hemodialysis (MHD), but it is still unclear how long this adverse effect will last. This study aims to investigate the impact of COVID-19 on the elevated anxiety symptoms of MHD patients one year after the outbreak. Assessment of elevated anxiety symptoms was performed on MHD patients during early COVID-19 (17 February- 29 February 2020) and one-year follow-up (1 March- 13 March 2021), and a total of 100 patients had completed face-to-face questionnaires at the first and one-year follow-up. At the beginning of the outbreak, 40 % of MHD patients had anxiety symptoms (Self-rating Anxiety Scale (SAS) score ≥ 50), and 11 % (SAS score: 60-69) and 2 % (SAS score ≥ 70) patients had moderate and severe anxiety symptoms respectively. Multivariate analysis shows that possibility of unaccompanied transfer, possibility of family members or themselves being infected in the hospital, added body temperature monitoring during dialysis, increased medical procedures are the risk factors for elevated anxiety symptoms during early COVID-19. At the one-year follow-up, the incidence of anxiety symptoms in the same group of patients declined to 28%, and all patients were mild anxiety symptoms (SAS score: 50-59), which is significantly lower than that of the early COVID-19 pandemic with statistically significant difference (p =0.003). Increased protective measures taken by the medical staves were the only risk factor for elevated anxiety symptoms during the one-year follow-up. This study shows that COVID-19 has a direct impact on the deterioration of anxiety symptoms in MHD patients. With the changes of the requirements for COVID-19 prevention and control, as well as the enhancement of propaganda and education of the pandemic and psychological care, the severity and risk factors of anxiety symptoms in MHD patients are changing. Thus, targeted interventions are suggested to improve the psychological endurance of the MHD patients.